Staff Training and Islamic Banks Performance: Evidence from Pakistan - Dr Zubair Ahmed Naseem; Dr Muhammad Azam (البصيرة)
Islamic banking is experiencing an extraordinary growth rate. As the number of Islamic banks increases, there is a need for well-trained employees. Especially in Pakistan, after the Federal Shariat Court decided to eliminate Reba from the Economy by the end of 2027, and the Parliament endorsed it by the 26th amendment in the constitution of Pakistan. This study was conducted to examine the effect of staff Training on the overall performance of Islamic banks and to determine the types of Trainings influence the performance of the Islamic banking institutions the most. After reviewing the already available literature, a questionnaire was developed and filled out by the employees of full-fledged Islamic Banks in Pakistan. A "one sample t-test" was applied. A test value of 4 was taken, and conclusions were drawn based on the p-value. Out of ten statements, six were accepted, indicating that the staff training positively influences the performance of Islamic banks. Currently major portion of Islamic finance consists of Islamic banking, but further expansion is the need of time. This study concluded that Islamic banks could improve their performance by increasing the effectiveness of their staff training.